Dampak Fintech Terhadap Perkembangan UMKM Ditinjau Dari Literasi Keuangan Dan Keamanan Data Para Pelaku UMKM Di Kota Gorontalo - Taufik Udango; Fitrianti; Parmin Ishak (Al-Buhuts, 2022)
The study is conducted to identify the direct and indirect connections of the financial and data security of people who target the use of fintech and their impact on the development of umkm in the city of gorontalo. The study USES a quantitative method. The methods of data collection used in the study are carried out through field observation, disseminating questionnaires, interviews, documentation and literature studies. As for the population in this research is the entire umkm perpetrator in the city of gorontalo with a withdrawal sample using sampling clusters. The data analysis technique used in the research is a path analysis technique with the help of version 24 of SPSS software. The study shows that (1) financial literacy has a positive and significant impact on the use of fintech in the food industry in north gorontalo city. (2) data security has a positive and significant impact on fintech use of the food industry in the north city of gorontalo. (3) indirect financial literacy has a positive and significant impact on the development of umkm through fintech in the development of the food industry in the north city of gorontalo. (4) indirect data security has an adverse positive impact on the development of umkm through fintech at the food industry in the north city of gorontalo. (5) fintech has a positive and significant impact on developers.